EXPLORING EFFECTIVE METHODOLOGIES IN TEACHING ENGLISH: ENHANCING LANGUAGE LEARNING - Babayeva Irada Sabirovna (Zeta Repository, 2023)
This article explores effective methodologies in teaching English, providing an overview of prominent approaches such as Communicative Language Teaching, Task-Based Language Teaching, Content-Based Instruction, the Lexical Approach, Total Physical Response, the Audio-Lingual Method, Task-Based Language Learning, and Content and Language Integrated Learning. It discusses the key principles, advantages, and challenges associated with each methodology, highlighting their impact on language acquisition and proficiency.